Job Satisfaction as a Mediator of the Effect of Psychological Empowerment and Organizational Culture on Employee Performance - Rahmat Rahmat; Asmawiyah Asmawiyah; Afiah Mukhtar (CV. Sakura Digital Nusantara, 2026)
Purpose – This study aims to analyze the effect of psychological empowerment and organizational culture on employee performance, with job satisfaction as a mediating variable at the Maros Regency Health Office. Design/methodology/approach – This research employed a quantitative correlational design. The population consisted of all employees of the Maros Regency Health Office. Using purposive sampling, 147 respondents were selected. Data were collected through online questionnaires distributed via Google Forms and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Finding/Results – Indicate that psychological empowerment has a significant positive effect on job satisfaction and employee performance. Organizational culture has a significant effect on job satisfaction but does not directly influence employee performance. Job satisfaction significantly affects employee performance and serves as a mediating variable in the relationships among psychological empowerment, organizational culture, and performance. Originality/Value – This study provides an empirical contribution regarding the role of job satisfaction as a mediating variable in the relationship between psychological empowerment, organizational culture, and employee performance in the government health sector, particularly in the Maro District Health Office, thus providing a more comprehensive understanding of the factors that influence employee performance.